PENGARUH GAYA KEPEMIMPINAN DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA FIRMA BINTANG TIMUR LAW OFFICE DI DEPOK - Anggi Aulia Arsyad; Anggada Bayu Seta (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of leadership style and communication on employee performance at the Bintang Timur Law Office Depok firm, both partially and simultaneously. The sampling technique in this study used a non-probability sampling technique, namely a saturated sample with a total of 63 respondents taken from all divisions in the company. The data analysis techniques used were: validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple regression test, simultaneous correlation coefficient test, simultaneous determination coefficient test, T test and F test. Partial hypothesis testing of the Leadership Style variable (X1) obtained a calculated T value> T table (4.639> 2.00) and a significance value of 0.00 <0.05. This means that Leadership Style (X1) has a significant effect on Employee Performance (Y). Partial hypothesis testing of the Communication variable (X2) obtained a calculated T value> T table (2.758> 2.00) and a significance value of 0.008 <0.05. This means that Communication (X2) has a significant effect on Employee Performance (Y). Simultaneous hypothesis testing obtained a calculated F value > F table (19.975 > 2.760) and a significance value of 0.000 < 0.05. So it can be concluded that Leadership Style (X1) and Communication (X2) have a significant effect both partially and simultaneously on Employee Performance (Y) of Bintang Timur Law Office Depok Firm.